Risk factors predisposing to congenital heart defects - Faheem Ul Haq; Fatima Jalil; Saman Hashmi; Maliha Iqbal Jumani; Aamer Imdad; Mehnaz Jabeen; Javad Tauseef Hashmi; Furqan Bin Irfan; Muhammad Imran; Mehnaz Atiq (Wolters Kluwer Medknow Publications, 2011)
Introduction: Congenital heart disease (CHD) is associated with multiple risk factors, consanguinity may be one such significant factor. The role of consanguinity in the etiology of CHD is supported by inbreeding studies, which demonstrate an autosomal recessive pattern of inheritance of some congenital heart defects. This study was done to find out the risk factors for CHD. Methods: A case-control study was done on pediatric patients at a tertiary care hospital, Aga Khan University Hospital, located in Karachi, Pakistan. A total of 500 patients, 250 cases and 250 controls were included in the study. Results: Amongst the 250 cases (i.e. those diagnosed with CHD), 122 patients (48.8%) were born of consanguineous marriages while in the controls (i.e. non-CHD) only 72 patients (28.9%) showed a consanguinity amongst parents. On multivariate analysis, consanguinity emerged as an independent risk factor for CHD; adjusted odds ratio 2.59 (95% C. I. 1.73 - 3.87). Other risk factors included low birth weight, maternal co-morbidities, family history of CHD and first born child. On the other hand, medications used by the mother during the index pregnancy, maternal age and gender of the child did not significantly increase the risk of developing CHD. Conclusions: Analyses of our results show that parental consanguinity, family history of CHD, maternal co-morbidities, first born child and low birth weight are independent risk factors for CHD.